2006
DOI: 10.1097/01.gme.0000227401.98933.0b
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparative study of the effects of oral and topical estrogen therapy on the vaginal vascularization and sexual function in hysterectomized postmenopausal women

Abstract: The results of our study suggest that ET alone in hysterectomized postmenopausal women increases the vaginal blood flow and improves some domains of sexual function, but it may not have an impact on diminished sexual desire or activity. Compared with systemic therapy, topical vaginal preparations are found to correlate with better symptom relief despite the lower serum level of estradiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 17 publications
3
64
0
7
Order By: Relevance
“…A recent study demonstrated that a conjugated estrogens dose of 0.3 mg is effective in treating postmenopausal women with atrophic vaginitis when administered either twice weekly or once daily (21 days on/7 days off) (3). Although earlier studies measured plasma estrogen concentrations after vaginal administration (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), it was not known whether use at this low dose would sufficiently minimize systemic exposure. Previous studies evaluating 0.3 mg conjugated estrogens found concentrations to be at or slightly above baseline values (6,8,13).…”
mentioning
confidence: 95%
“…A recent study demonstrated that a conjugated estrogens dose of 0.3 mg is effective in treating postmenopausal women with atrophic vaginitis when administered either twice weekly or once daily (21 days on/7 days off) (3). Although earlier studies measured plasma estrogen concentrations after vaginal administration (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), it was not known whether use at this low dose would sufficiently minimize systemic exposure. Previous studies evaluating 0.3 mg conjugated estrogens found concentrations to be at or slightly above baseline values (6,8,13).…”
mentioning
confidence: 95%
“…This local therapy has few systemic adverse effects compared to systemic administration, although vaginal estrogen is absorbed into the serum at low levels [7]. Vaginal estrogens are initially prescribed at an initial priming dose, followed by a maintenance dose of the minimal dose needed.…”
Section: Types Of Estrogen Replacementmentioning
confidence: 98%
“…In this subset, most patients also suffered from recurrent bacterial cystitis (14%). Menopause is associated with a reduction in estrogens at the genital level [21][22][23]. An inadequate estrogen supply may be coupled with recurrent UTI, chronic urethritis, vestibule and vaginal atrophy, and insufficient vaginal lubrication, which are frequently associated with discomfort and pain during sexual activity.…”
Section: Luts and Sds In Womenmentioning
confidence: 99%